Estudio y aplicación del crédito documentario para la exportación de los productos agrícolas de la unidad económica, popular y solidaria de Quiroga (UEPQ) hacia el bloque Mecosur. - Gualacata Quilumba, María Esther (2015)
This project aims to inform producers Economic Unity , and People's Solidarity Quiroga ( UEPQ ) and in conjunction with other associations such as : Agricultural Center Antonio Ante, Consortium of Agricultural and Livestock of Imbabura and Carchi COPCAVIC , Pueblo Board of Irrigation agricultural Pimampiro about foreign trade and export procedures for agricultural products ( yellow corn ) applying the letter of credit for export to Mercosur ( Venezuela ) .For the development of this proposal took into account the structure of four chapters; theoretical foundation, diagnosis, description of the research process and presentation of results and impact analysis. In the first chapter the theoretical foundations that support project-related aspects of the non-tariff trade, international market, logistics, international physical distribution, barreas tariff and among other topics. In the second chapter it has been taken into account research techniques such as surveys and interviews. Which they are aimed at producing unit also administrator, inspector and director IEPS. Also secondary information was obtained as documents UEPQ who provided for conducting research. Export trade statistics and yellow corn in which variables in each of the Mercosur countries to identify the potential for yellow maize export market was investigated included. Once the information I was tabulated and analyzed surveys to determine the strengths, weaknesses, threats and opportunities and consequently realize the strategic crossroads SWOT. For the third chapter the project proposal in which an export plan consists of steps designed arises. The first phase is the description of the association, the second phase of the product to be exported, in the third phase contains analysis of the target market, the fourth phase is the proposed distribution of the documentary credit and detailed in the fifth phase results in the exportable supply of yellow corn and sales projections for the following years is determined. A detailed plan to determine whether the project is feasible for Economic Unit Quiroga analysis was performed.